P063/O11 Inhibition of arginase-1 expression by the transcription factor Fra-1 in macrophages exacerbates rheumatoid arthritis inflammation. (March 2019) - Hannemann, N; Cao, S; Schnelzer, A; Jordan, J; Eberhardt, M; Schleicher, U; Uebe, S; Ekici, A; Rech, J; Bäuerle, T; Bogdan, C; Vera, J; et al.
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: The activator protein (AP)-1 transcription factor family, especially its subfamily of FOS proteins (cFos, FosB, Fra-1 and Fra-2) are associated to the regulatory network of macrophage responses. Moreover, it is well known that macrophages are central player during rheumatoid arthritis (RA). Objectives: This study aims to delineate the role of Fra-1 in macrophages during the acute destructive inflammatory phase of RA. Methods: Therefore, we applied the serum-induced arthritis (K/BxN) model to Fra-1 deficient mice controlled by the Mx1 promoter (Fra-1 ΔMx ) or the LysM promoter (Fra-1 ΔLysM ). Moreover, we performed in vitro analyses of macrophage polarization in wildtype and Fra-1 deficient macrophages, as well as micro-arrays and ChIP sequencing analyses to delineate Fra-1 targets in activated macrophages. We completed our analysis by studying Fra-1 expression in RA patients' synovium. Results: Fra-1 mutant mice had decreased arthritis severity compared to their littermate wildtype mice. The alleviated arthritis was accompanied to increased arginase-1 (Arg1) expression and activity in the joints, suggesting that its anti-inflammatory features milder RA inflammation. Sorting of immune cell populations revealed macrophages as the major source of Arg1, which was increased in Fra-1 mutant mice. Mechanistically, Fra-1 transcriptionally inhibited Arg1 expression in macrophages. Moreover, inhibition of Arginase in Fra-1 mutant mice restored a full blunt inflammatory RA response and the supplementation of mice with l-arginine, leading to increased arginase activity in the joint, is sufficient to milder arthritis. Synovium histological sections from RA patients showed a correlation between Arg1, Fra-1 and the DAS28 score, confirming that increased Arg1 activity is of benefit also for human inflammatory joint disease. Conclusions: Our data show for the first time that Fra-1 is a pivot between pro- and anti-inflammatory macrophage. By inhibiting Arg1 activity, Fra-1 exacerbates RA inflammation and joint destruction. Disclosure of Interest: None declared.